Barns utemiljöer i Hebron : gestaltningsverktyg för barnperspektiv implementerat på Al Ibrahimyye plats - Hagströmer, Elisabeth (SLU/Landscape Architecture (until 121231), 2009)
This is a final thesis for the Master’s Programme in Landscape Architecture at the Faculty of Landscape Planning, Horticulture and Agricultural Science. The subject of the thesis is the outdoor environment of children in Hebron.